2018
DOI: 10.1111/ecc.12876
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to care for breast cancer: A qualitative study in Ireland

Abstract: Disparities in survival after breast cancer persist. Cancer registry data that are often used to assess associated factors only explain some of the differences. The purpose of this study was to obtain information from disadvantaged Irish women concerning possible barriers to care for breast cancer above and beyond risk factors collected by cancer registries. We used a qualitative interview study with disadvantaged women in treatment for breast cancer, following the methods of thematic analysis. Important theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Yet, even for those who have public medical coverage, people who experienced socioeconomic disadvantage found it more challenging to afford out-of-pocket expenses or hidden costs directly required for their treatment such as supportive care drugs, nutrition supplements, access to allied health resources, childcare to attend appointments, transportation, and travel expenses (i.e., food, lodging, gas, parking) [ 68 – 71 , 73 75 ]. Consequently, not having these necessary supports led to higher rates of non-adherence [ 74 , 75 ] and/or meant that systemic therapy was poorly tolerated [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, even for those who have public medical coverage, people who experienced socioeconomic disadvantage found it more challenging to afford out-of-pocket expenses or hidden costs directly required for their treatment such as supportive care drugs, nutrition supplements, access to allied health resources, childcare to attend appointments, transportation, and travel expenses (i.e., food, lodging, gas, parking) [ 68 – 71 , 73 75 ]. Consequently, not having these necessary supports led to higher rates of non-adherence [ 74 , 75 ] and/or meant that systemic therapy was poorly tolerated [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In high-income countries, the cancer care system often has supportive care resources (e.g., nutrition, patient and family counselling, psychiatry, social work, speech-language pathology, physiotherapy) to assist patients undergoing treatment. However, three studies cited there is a scarcity of resources and lack expertise to support patients who experience socioeconomic disadvantage and whose social care needs may also go unnoticed by HCPs [ 70 , 72 , 73 ]. For example, Lineback and colleagues [ 70 ] found that although patients with less favorable socioeconomic circumstances with esophageal cancer were provided with a care team such as a case manager or social worker, the cancer hospital itself was less able to solve multiple issues arising from mistrust, poor communication, and financial strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several new treatments for mBC have been recently introduced [ [12] , [13] , [14] , 16 ], positive outcomes depend not only on the response to treatment, which varies according to disease and patient characteristics, but also on access to those treatments, which is affected by a host of factors. The wide variation in these factors leads to disparities in cancer care between and within countries, including high-income countries, and not all patients benefit equally from the healthcare services available [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. For example, registry data from New Zealand found that the median survival after mBC diagnosis was 18.8 months (2010–2015), around half that of other developed countries [ 27 ].…”
Section: Introductionmentioning
confidence: 99%